PREPARATION OF TEST INSTRUMENTS BASED ON HIGHER ORDER THINKING SKILLS AT UPT SPF SDI MANNURUKI 2 MAKASSAR - Nashruddin; Roslina; Waliyudin (Jurnal Abdimas Ilmiah Citra Bakti, 2024)
The background for implementing this community service activity is the lack of understanding of teachers about Higher Order Thinking Skill (HOTS) based tests. This activity aims to improve the ability of teachers at UPT SPF SDI Mannuruki 2 Makassar in the pedagogical competence and professional competence aspects, specifically the ability to prepare Higher Order Thinking Skill (HOTS) based test instruments to be applied to their students. The activity methods are observation and interview, preparation of materials, preparation of supporting data, implementation of activities consisting of training and discussion. The participants were 14 teachers at UPT SPF SDI Mannuruki 2 Makassar, consisting of 12 classroom teachers and 2 subject teachers. At the end of the activity, 11 participants were succeeded in compiling HOTS-based test instruments, but there were 3 participants who did not understand how to compose the HOTS-based test instrument. This indicates that the participants have pedagogical competence and professional competence, because they generally understand and can implement HOTS-based test instruments for students.